Dark comets: the cosmic catastrophic threat to earth - Khalil, M.; Said, M.; Osman, H.; Younis, N.; Khaled, N.; Amr, Y.; A. Mohamed, N.; Ibrahim, A. (International Journal of Advanced Astronomy, 2020)
Dark Comets are catastrophic hazardous objects that could hit Earth without warning. There are thousands of such unseen comets buzzing around. Very few of which are known. An overview of the dark comets deadly threat is presented in this paper. Moreover, detection techniques of these invisible objects are discussed.Â Â